Analisis Efektivitas dan Konstribusi Penerimaan Pajak BEA Perolehan Hak Atas tanah dan Bangunan BPHTB DAN PBB-P2 terhadap PAD di Kabupaten Aceh Selatan - Fitria Ratna Lingga; Nurlaila Nurlaila (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to find out how the level of effectiveness and contribution of tax revenue from Land and Building Rights Acquisition Tax (BPHTB) to Regional Original Income (PAD). The analytical method used is primary data (observation results) and secondary data (data from agencies and interviews). The results showed that in Aceh selatanRegency the level of effectiveness of BPHTB tax revenues was categorized as very effective in 2021, while in 2019 BPHTB tax revenues were categorized as less effective and the contribution to land and building rights acquisition fees (BPHTB) during 2021 was categorized as good. The South Aceh District Government must be more active in collecting Land and Building Acquisition Fees (BPHTB) so that its contribution can increase